Pengaruh Kepuasan Kerja, Stres Kerja, Dan Lingkungan Kerja Terhadap Turnover Intension pada Karyawan Operator PT. Berkat Citra Lestari, Samarinda - Dedi Setiawan Wibowo; Widi Dewi Ruspitasari Ruspitasari; Yunus Handoko (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine: 1) the effect of job satisfaction on employee turnover intention at PT. Berkat Citra Lestari, 2) the effect of work stress on employee turnover intention at PT. Berkat Citra Lestari, and 3) the effect of work environment on employee turnover intention at PT. Berkat Citra Lestari. The population in this research was all operator employees of PT. Berkat Citra Lestari as 50 people with the total sample of 40 people collected using the random sampling method. The variables of this research consist of independent variables which are job satisfaction (X1), job stress (X2), and work environment (X3) and the dependent variable is employee turnover intention (Y). The data collection method used in this research are observation, interview, and questionnaire. The data analysis method used in this research are descriptive analysis and multiple linear regression methods. Based on the results of the research, it was concluded that: Job satisfaction has no effect on turnover intention, in the sense that the higher the job satisfaction, the lower the possibility of employees in terms of turnover intention.Job stress affects turnover intention, in the sense that the higher the job stress, the higher the possibility of employees in terms of turnover intention. Work environment has no effect on turnover intention, in the sense that the higher the acceptance of the work environment, the lower the possibility of employees in terms of turnover intention.